Li-ion batteries with enhanced electrochemical stability window
By incorporating antisolvents like amides into aqueous electrolytes, the electrochemical stability window of lithium ion batteries is expanded to 3.0 V, achieving high ionic conductivity and non-flammability, addressing the limitations of existing technologies.
Patent Information
- Application Number
- JP2024559107
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-12-16
- Publication Date
- 2024-12-26
AI Technical Summary
Existing methods for increasing the electrochemical stability window of lithium ion batteries, particularly aqueous electrolytes, are either costly, result in flammable compositions, or use organic solvents that are immiscible with water, failing to maintain non-flammability and efficiency.
The addition of specific antisolvents, such as amides, to aqueous electrolytes reduces water activity and forms a strong solid-electrolyte interface (SEI), enhancing ionic conductivity and lowering viscosity while maintaining non-flammability, thereby expanding the electrochemical stability window.
The electrochemical stability window is expanded to at least 3.0 V, achieving high ionic conductivity and low viscosity, with improved coulombic efficiency and capacity retention, and the electrolytes remain non-flammable, making them safer and more cost-effective.
Smart Images

Figure 2024547223000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to U.S. Provisional Application No. 63 / 265,767, filed December 20, 2021, which is incorporated by reference in its entirety.
[0002] [STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT] This invention was made with Government support under Grant No. DEAR0000389 awarded by the Department of Energy (DOE ARPA-E). The Government has certain rights in this invention.
[0003] The present disclosure relates to compositions and methods for increasing the electrochemical stability of batteries. In some embodiments, the compositions and methods of the present disclosure provide lithium ion batteries with an electrochemical stability window greater than 3.0 V. [Background technology]
[0004] Recent "solvent-in-salt" electrolytes, i.e. "water-in-salt electrolytes (WISE)" for aqueous batteries and "ultra-concentrated electrolytes" for non-aqueous batteries, are a major breakthrough for both aqueous and non-aqueous systems. The numerous salt aggregates (AGGs) in the "solvent-in-salt" electrolytes allow the salt to selectively decompose into the solvent to form a robust interfacial layer on the electrode, greatly expanding the electrochemical window. Unfortunately, the high salt concentration itself inevitably increases the viscosity and cost of the electrolyte.
[0005] To reduce the amount of salt used, anti-solvents have also been added to electrolyte compositions. Typically, anti-solvents are selected to dissolve the solvent (e.g., be miscible with the solvent) but not dissolve the salt. Without being bound by any theory, it is believed that the addition of anti-solvents to ultra-concentrated non-aqueous electrolytes results in the formation of "locally concentrated electrolytes". These locally concentrated electrolytes inherit almost all the benefits of the low viscosity and low cost of ultra-concentrated electrolytes because the anti-solvents maintain a low amount of solvent and high salt AGG in the Li-ion solvation sheath. However, the addition of anti-solvents that do not dissolve lithium ions also reduces lithium ion conductivity.
[0006] Extensive research has also been conducted on water-in-salt electrolytes in an attempt to expand the electrochemical stability window. Various methods have been used in an attempt to increase the electrochemical stability window of aqueous lithium electrolytes, such as (i) increasing the salt concentration in the hydrate molten electrolyte to 27.7 m to reduce the H2O molecules in the Li-ion solvation sheath, (ii) adding additives to produce a 28 m "water-in-two-salt" electrolyte, (iii) using mixed cation electrolytes to produce a 40 m electrolyte, (iv) utilizing a 55.5 m lithium salt monohydrate, and (v) adding ionic liquid to WISE to produce a 63 m electrolyte.
[0007] Using 63 m electrolytes in batteries is costly due to the need to add ionic liquids and large amounts of electrolyte salt to these electrolytes. Furthermore, even when using electrolytes with a salt concentration of 63 m, the cathodic potential of WISEs only extends or decreases to 1.75 V, with an overall electrochemical stability window of 3.25 V. An alternative way to reduce the amount of water in WISEs is to add organic solvents or gel polymers that can dissolve both salt and solvent in large amounts. Unfortunately, these organic solvents and gel polymers are also flammable, which reduces the benefits of aqueous electrolytes. The poor solvents (e.g., HFE, TTE, TFEO) used in non-aqueous electrolytes for "localized high concentration electrolytes" are completely (i.e., more than 90% or alternatively more than 92.5%, typically more than 95% or alternatively more than 97.5%, often more than 99% or alternatively more than 99.25%, most often more than 99.5%) immiscible with WISEs and therefore cannot be used in aqueous electrolytes. Thus, conventional methods for increasing the electrochemical stability window are (i) expensive, (ii) result in flammable compositions, and / or (iii) use organic solvents that are immiscible with water.
[0008] Thus, there remains a need for methods of increasing the electrochemical stability window of aqueous electrolyte compositions that reduce the amount of water molecules within the lithium ion solvation sheath in the aqueous electrolyte composition while maintaining the non-flammable properties of the aqueous lithium ion electrolyte composition. Summary of the Invention
[0009] To date, further depletion of water molecules within the Li-ion solvation sheath through ultra-concentration strategies while maintaining the non-flammable properties of aqueous lithium-ion electrolyte compositions has not been achieved due, at least in part, to the limitations of the precipitation / dissolution equilibrium of lithium salts.
[0010] The inventors have discovered that the addition of certain classes of anti-solvents can easily produce dilute aqueous electrolytes that go beyond WISE, with wider electrochemical stability windows and lower costs, while still remaining non-flammable. In general, the compositions and methods of the present disclosure provide one or more of the following advantages over conventional methods: (i) the addition of anti-solvents disclosed herein results in the disclosed aqueous electrolytes having salt-like properties, including strong binding with H2O molecules, which reduces water activity and / or removes water from the Li-ion solvation sheath; (ii) the addition of anti-solvents disclosed herein increases the ability to form a strong SEI, thereby lowering the cathodic limiting potential to about 1.5 V or less (e.g., Li4Ti5O 12 (iii) the poor solvent is capable of dissolving a small amount of lithium salt, thus making it fully miscible with the WISE, but allowing the overall salt concentration to be reduced so that the electrolyte is less than 10 -3 2. To enable the electrolyte to have high ionic conductivity, exceeding 100 S / cm, and low viscosity. Furthermore, typically the poor solvents or diluents used in the present disclosure are inexpensive and non-flammable, thereby maintaining the non-flammability of the electrolyte.
[0011] As used herein, the term "capable of dissolving small amounts of lithium salts" means that the solubility of lithium ions in the antisolvents of the present disclosure is about 1.0 g / L or less, or alternatively about 0.9 g / L or less, or alternatively about 0.8 g / L or less, or alternatively about 0.7 g / L or less, or alternatively about 0.6 g / L or less, typically about 0.5 g / L or less, or alternatively about 0.4 g / L or less, or alternatively about 0.3 g / L or less, often 0.25 g / L or less, or alternatively about 0.2 g / L or less, or alternatively about 0.15 g / L or less, often 0.1 g / L or less. The term "anti-solvent" is used to describe an additive added to an aqueous solution of a lithium-ion electrolyte that is miscible with water but does not dissolve lithium salts or lithium ions, i.e., the solubility of lithium salts or lithium ions is about 0.5 g / L or less, or alternatively about 0.4 g / L or less, or alternatively about 0.3 g / L or less, typically about 0.25 g / L or less, or alternatively about 0.2 g / L or less, or alternatively about 0.15 g / L or less, often 0.1 g / L or less, or alternatively about 0.075 g / L or less, or alternatively about 0.05 g / L or less, or alternatively about 0.025 g / L or less, or alternatively about 0.015 g / L or less, often 0.01 g / L or less. The term "miscible" means that the solubility of the anti-solvent in water is at least about 1 g / L, typically at least about 10 g / L, often at least about 100 g / L, and most often at least about 500 g / L.
[0012] One particular aspect of the present disclosure provides an aqueous electrolyte composition for a lithium ion battery, comprising an electrolyte salt comprising a lithium salt, water, and an organic compound miscible with water as a poor solvent.
[0013] In some embodiments, the organic compound is a protic compound. In other embodiments, the organic compound is an amide. In yet other embodiments, the organic compound has the formula: R 1 -C(=O)-NR 2 R 3 I (In the formula, R 1 is a C1-C4 alkyl, C3-C6 cycloalkyl or a moiety of formula -X, X is -OR a , -NR b R c or -SR a and R a are each H or C1-C4 alkyl, R b , R c , R 2 and R 3 each is independently H or C1-C4 alkyl.
[0014] In yet another embodiment, the lithium salt comprises LiCl, LiPF, Li2SO, LiN(SO2CF3), LiN(SO2CH3), LiN(SO2C4H9), LiN(SO2C2F5), LiN(SO2C4F9), LiN(SO2F3)(SO2C4F9), LiN(SO2C2F4SO2), LiN(SO2F), LiN(SO2F)(SO2CF3), LiNO, LiBF, LiCF3SO3, or combinations thereof. In one particular embodiment, the lithium salt comprises LiN(SO2CF3). In yet another particular embodiment, the lithium salt comprises LiPF, LiSO3CF3, or combinations thereof.
[0015] In other embodiments, the electrolyte salt further comprises a magnesium salt. Exemplary magnesium salts that may be used as electrolytes in the present disclosure include, but are not limited to, MgSO4, MgCl2, Mg(NO3)2, other magnesium salts known to those of skill in the art, and combinations thereof.
[0016] In yet other embodiments, the molarity of the electrolyte salt ranges from about 6 m to about 5.75 m, or alternatively from about 5.75 m to about 5.5 m, or alternatively from about 5.5 m to about 5.25 m, or alternatively from about 5.25 m to about 5.0 m, or alternatively from about 5.0 m to about 4.75 m, or alternatively from about 4.75 m to about 4.5 m, or alternatively from about 4.5 m to about 4.25 m, or alternatively from about 4.25 m to about 4.0 m, or alternatively less than about 4.0 m. In one particular embodiment, the molarity of the electrolyte salt is about 4.5 m.
[0017] In yet another embodiment, the aqueous electrolyte composition is non-flammable.
[0018] Another aspect of the present disclosure provides a rechargeable lithium-ion battery comprising a cathode, an anode, and an electrolyte composition disclosed herein, e.g., an electrolyte comprising an electrolyte salt, water, and another compound miscible with water as a poor solvent. As used herein, the terms "disclosed herein," "defined herein," and "described herein" when referring to a variable, composition, or method, are used interchangeably herein and incorporate by reference the broad definition as well as the narrower definition(s), if any. Thus, for example, a battery including an electrolyte salt "as disclosed herein" means (i) a battery including a lithium salt as the electrolyte, (ii) a battery including LiCl, LiPF, Li2SO, LiN(SO2CF3), LiN(SO2CH3), LiN(SO2C4H9), LiN(SO2C2F5), LiN(SO2C4F9), LiN(SO2F3)(SO2C4F9), LiN(SO2C2F5)(SO2C4F9), LiN(SO2C2F4SO2), LiN(SO2F), LiN(SO2F)(SO2CF3), LiNO, LiBF, LiCF3SO3, or combinations thereof, (iii) a battery including LiN(SO2CF3), and (iv) a battery including LiPF, LiSO3CF3, or combinations thereof.
[0019] In some embodiments, the amount of anti-solvent present in the aqueous electrolyte compositions of the present disclosure is in the range of 5:1 to 5.5:1 relative to the amount of water, or alternatively 5.5:1 to 6:1, or alternatively 6:1 to 6.5:1, or alternatively 6.5:1 to 7:1, or alternatively 7:1 to 7.5:1, or alternatively 7.5:1 to 8:1, or alternatively 8:1 to 8.5:1, or 8.5:1 to 9:1, or at least about 9:1 v / v.
[0020] In some embodiments, the electrochemical stability window of the electrolyte composition of a lithium ion battery is at least about 3.0 V, or alternatively about 3.0 V to about 3.1 V, or alternatively about 3.1 V to about 3.2 V, or alternatively about 3.2 V to about 3.3 V, or alternatively about 3.3 V to about 3.4 V, or alternatively more than about 3.3 V. When referring to a numerical value, the terms "about" and "approximately" are used interchangeably herein and refer to being within an acceptable error range for the particular value as determined by one of ordinary skill in the art. The determination of such a value depends, at least in part, on the limitations of the method by which the value is measured or determined, e.g., the measurement system, i.e., the degree of precision required for a particular purpose. For example, the term "about" can mean within or more than one standard deviation, as is customary in the art. Alternatively, the term "about" when referring to a numerical value can mean ±20%, typically ±10%, often ±5%, and more often ±1% of the numerical value. Generally, however, when a specific value is recited in the present application and claims, unless otherwise specified, the term "about" means within an acceptable range of error, typically within one standard deviation, for the particular value.
[0021] In yet other embodiments, the aqueous electrolyte composition further comprises a hydroxide. Exemplary hydroxides that may be used in the aqueous electrolyte compositions of the present disclosure include, but are not limited to, KOH, NaOH, LiOH, and any other alkali, alkaline earth, and transition metal hydroxides known to one of ordinary skill in the art, and mixtures thereof.
[0022] In yet other embodiments, the molarity of the electrolyte salt in the electrolyte composition is as defined herein. In one particular embodiment, the molarity of the electrolyte salt in the electrolyte composition is less than about 5 m.
[0023] In other embodiments, the rechargeable lithium ion battery is a pouch cell lithium ion battery or a coin cell lithium ion battery.
[0024] In further embodiments, the coulombic efficiency of the rechargeable lithium ion battery is at least about 85%, typically at least about 90%, often at least about 95%, more often at least about 99%, and most often greater than 99%, or alternatively from about 99.90% to about 99.92%, or alternatively from about 99.92% to about 99.94%, or alternatively from about 99.94% to about 99.96%, or alternatively from about 99.96% to about 99.98%, or greater than about 99.98% after 5 cycles.
[0025] In still other embodiments, the capacity retention of the rechargeable lithium ion battery after 500 cycles is about 60%-65%, or alternatively about 65%-70%, or alternatively about 70%-75%, or alternatively about 75%-80%, or alternatively about 80%-85%, or alternatively about 85%-90%, or alternatively about 90%-95%, or alternatively at least about 95%. In one particular embodiment, the capacity retention of the rechargeable lithium ion battery after 500 cycles is at least about 90%.
[0026] Yet another aspect of the present disclosure provides a rechargeable lithium-ion battery that includes a cathode, an anode, and an aqueous electrolyte composition having an electrochemical stability window as described herein (e.g., greater than 3.0 V) and a molar concentration of electrolyte salt in the aqueous electrolyte composition as described herein (e.g., less than 5 m).
[0027] In some embodiments, the aqueous electrolyte composition includes a lithium electrolyte salt, water, and a water-miscible anti-solvent. Optionally, the anti-solvent is an organic compound, and further, the electrolyte composition is non-flammable.
[0028] In yet other embodiments, the antisolvent reduces the cathodic limiting potential by about 0.01 V to about 0.05 V, or alternatively by about 0.05 V to about 0.10 V, or alternatively by about 0.10 V to about 0.15 V, or alternatively by about 0.15 V to about 0.20 V, or alternatively by at least about 0.2 V.
[0029] In yet another embodiment, the anti-solvent comprises an amide compound. Exemplary amide compounds that can be used as anti-solvents include, but are not limited to, urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, and other derivatives thereof and combinations thereof.
[0030] In further embodiments, the aqueous electrolyte composition further comprises a hydroxide. Exemplary hydroxides that may be used in the aqueous electrolyte compositions of the present disclosure are described above.
[0031] A further aspect of the present disclosure provides a method of increasing the electrochemical stability window of a lithium ion battery comprising an aqueous lithium electrolyte solution. The method comprises adding a water-miscible anti-solvent. In some embodiments, the anti-solvent comprises an amide compound. In one particular embodiment, the amide compound comprises those described herein, such as urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or combinations thereof.
[0032] In yet other embodiments, the amide compound is a compound of Formula I.
[0033] In yet other embodiments, the amount of the electrochemical stability window is increased by about 0.01 V to about 0.05 V, or alternatively about 0.05 V to about 0.10 V, or alternatively about 0.10 V to about 0.15 V, or alternatively about 0.15 V to about 0.20 V, or alternatively about 0.20 V to about 0.25 V, or alternatively about 0.25 V to about 0.30 V, or alternatively about 0.30 V to about 0.35 V, or alternatively about 0.35 V to about 0.40 V, or alternatively about 0.40 V to about 0.45 V, or alternatively about 0.45 V to about 0.50 V, or alternatively at least about 0.5 V.
[0034] Another aspect of the present disclosure provides a method of reducing the cathode limiting potential in a lithium battery containing an aqueous lithium electrolyte solution, comprising adding a water-miscible anti-solvent. In some embodiments, the anti-solvent comprises an amide compound. In still other embodiments, the stoichiometric amount of anti-solvent added relative to the amount of water added is about 1.5 to about 1.25, or alternatively about 1.25 to about 1.1, or alternatively about 1.1 to about 1.0, or alternatively about 1 or less. In still other embodiments, the amide compound comprises those described herein, such as urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or combinations thereof.
[0035] In further embodiments, the amide compound is a compound of formula I.
[0036] In yet other embodiments, the amount of cathodic limiting potential is decreased by at least about 0.1V.
[0037] It should be understood that throughout this disclosure, the combination of different or alternative embodiments described herein form other embodiments. For example, one particular method of the present disclosure for increasing electrochemical stability is described herein as having an increase in the electrochemical stability window in the range of about 0.05 V to about 0.10 V, and an added antisolvent stoichiometric amount in the range of about 1.25 to about 1.1 relative to the amount of water. Thus, the combination of these two different alternative embodiments provides a method for increasing the electrochemical stability window in the range of about 0.05 V to about 0.10 V by adding an amount of antisolvent in the range of about 1.25 to about 1.1 relative to the amount of water. In this manner, a wide variety of different embodiments of compositions and methods are embodied in the present disclosure. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 shows the liquid region in the ternary phase diagram of urea, LiTFSI, and HO at room temperature. [Diagram 2] This is a graph showing the coordination numbers of CO(NH2)2, TFSI, and H2O around Li+ (within 3.0 Å) for the 4.1 m, 4.5 m, and 5.1 m electrolytes compared to the 21 m WISE. [Diagram 3] A graph showing the pair distribution function (g(r)) and coordination number (n(r)) of 4.1 m CO(NH2)2-LiTFSI-H2O-0.1 m KOH electrolyte solution. B graph showing the pair distribution function (g(r)) and coordination number (n(r)) of 4.5 m CO(NH2)2-LiTFSI-H2O-0.1 m KOH electrolyte solution. [Figure 3-1] C 5.1 m CO(NH 2 ) 2 -LiTFSI-H 2 O-0.1 m KOH electrolyte solution pair distribution function (g(r)) and coordination number (n(r)). [Figure 4](i) Predicted reduction potentials (V vs. Li / Li+) from quantum chemical calculations and (ii) graph showing the overall electrochemical stability window of electrolytes with different LiTFSI concentrations and electrode redox, overlaid with a CV on the current collector, as well as a zoomed-in view of the region near the cathodic and anodic limits. [Diagram 5] 1A and 1B are graphs showing the cathodic and anodic limits of different aqueous electrolytes measured by LSV at a scan rate of 0.2 mV / s, respectively. [Figure 6] Cyclic voltammograms (scan rate = 1 mV / s) of an aluminum working electrode in 4.5 μm electrolyte with Pt as counter electrode and Ag / AgCl as reference electrode. [Figure 7] FIG. 1 is a schematic diagram of one possible mechanism for the formation of a hybrid inorganic / organic SEI. [Figure 8] A. Capacity as a function of cycles for 2.5 V LiMn2O4||Li4Ti5O12 and 2.6 V LiVPO4F||Li4Ti5O12 full cells with different lithium salt concentrations. B. Coulombic efficiency as a function of cycles for 2.5 V LiMn2O4||Li4Ti5O12 and 2.6 V LiVPO4F||Li4Ti5O12 full cells with different lithium salt concentrations. [Figure 8-1] C Long-term cycling stability of LiMn2O4||Li4Ti5O12 full cell at high current in 4.5 m electrolyte at 0.5 C. D Long-term voltage profile of LiMn2O4||Li4Ti5O12 full cell in 4.5 m electrolyte at 0.5 C. [Figure 9] A. Long-term cycling performance profile of a 1.5 mAh / cm2 LMO / LTO full cell in 4.5 m LiTFSI / NMA / H2O at 0.5 C. B. Long-term voltage profile of a 1.5 mAh / cm2 LMO / LTO full cell in 4.5 m LiTFSI / NMA / H2O at 0.5 C. [Figure 10]Figure 13. Cycling performance of LiVPO4F||Li4Ti5O12 full cell at 0.2 C in 4.5 m electrolyte with areal capacity of 1.5 mAh / cm2. [Figure 11] A. Long-term cycling performance profile of LiVPO4F||Li4Ti5O12 full cell at 0.5 C in 4.5 m electrolyte. B. Long-term voltage profile of LiVPO4F||Li4Ti5O12 full cell at 0.5 C in 4.5 m electrolyte. [Figure 12] FIG. 1 shows the electrolyte stability window of the electrolyte of the present disclosure compared to various aqueous electrolytes with different salt concentrations (conventional aqueous electrolyte, 21 m, 28 m, and 63 m). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] Some aspects of the present disclosure relate to aqueous electrolyte compositions that include a non-flammable anti-solvent. In particular, the addition of an anti-solvent (sometimes referred to as a diluent or additive) of the present disclosure (i) reduces the activity of water and / or results in an aqueous electrolyte with salt-like properties, including strong binding with HO molecules, which removes water from the Li-ion solvation sheath, (ii) increases the ability to form a strong SEI, thereby lowering the cathodic limiting potential (e.g., to about 1.7 V or less, in some embodiments to about 1.6 V or less, and in other embodiments to about 1.5 V or less), and / or (iii) improves the electrolyte's ability to withstand high temperatures above 1000°C. -3 This allows the electrolyte to have high ionic conductivity, greater than 100 S / cm, and low viscosity. Additionally, the typical anti-solvents used in the present disclosure are inexpensive and non-flammable, so that the cost remains relatively the same and the electrolyte remains non-flammable. In some specific embodiments, the anti-solvent is salt-like. As used herein, the term "salt-like" refers to an anti-solvent that is solid at room temperature but dissolves or is miscible with water.
[0040] Various features and advantages of the present disclosure are described using some specific electrolyte compositions. However, it should be understood that the scope of the present disclosure is not limited to these specific electrolyte compositions. Indeed, a wide variety of electrolyte compositions are embodied within the scope of the present disclosure, as expressly disclosed herein. The following discussion of various results, features and advantages is provided by way of example only and is not intended to limit the scope thereof.
[0041] Some aspects of the present disclosure are based on the discovery by the inventors that the addition of a poor solvent, particularly an organic compound as a poor solvent, to an aqueous electrolyte composition results in an electrolyte composition with a significantly increased or widened electrochemical stability window. In some embodiments, the electrochemical stability window of a lithium ion battery comprising an electrolyte composition of the present disclosure is at least about 3.0 V, or alternatively about 3.0 V to about 3.1 V, or alternatively about 3.1 V to about 3.2 V, or alternatively about 3.2 V to about 3.3 V, or alternatively about 3.3 V to about 3.4 V, or alternatively greater than about 3.3 V.
[0042] To determine the effect of adding a poor solvent of the present disclosure, an aqueous electrolyte composition comprising 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O was prepared and tested. The addition of an organic compound as a poor solvent resulted in an electrolyte composition with an expanded electrochemical stability window of 3.3 V. Alternatively, the addition of a poor solvent of the present disclosure increased the electrochemical stability window by at least about 0.2 V, in other embodiments by at least about 0.3 V, in still other embodiments by at least about 0.4 V, and in other embodiments by at least about 0.5 V, compared to the same electrolyte composition in the absence of a poor solvent of the present disclosure.
[0043] In yet other embodiments, the addition of an anti-solvent of the present disclosure lowered the cathodic limiting potential to about 1.7 V to about 1.6 V, or alternatively, to about 1.6 V to 1.5 V, or alternatively, to about 1.5 V or less. Alternatively, the addition of a poor solvent of the present disclosure reduced the cathodic limiting potential by about 0.01 V to about 0.05 V, or alternatively about 0.05 V to about 0.10 V, or alternatively about 0.10 V to about 0.15 V, or alternatively about 0.15 V to about 0.20 V, or alternatively about 0.20 V to about 0.25 V, or alternatively about 0.25 V to about 0.30 V, or alternatively about 0.30 V to about 0.35 V, or alternatively about 0.35 V to about 0.40 V, or alternatively about 0.40 V to about 0.45 V, or alternatively about 0.45 V to about 0.50 V, or alternatively at least about 0.5 V, compared to the same electrolyte composition in the absence of a poor solvent of the present disclosure.
[0044] In yet another embodiment, detailed studies have shown that the addition of a poor solvent can reduce the Li + It has been shown to reduce the number of HO in the solvation shell from 2.6 in WISE to about 2.0 or less, typically about 1.5 or less, often about 1.0 or less, and most often about 0.7 or less. Alternatively, the addition of the antisolvent of the present disclosure reduces the number of HO in the solvation shell from 2.6 in WISE to about 2.0 or less, typically about 1.5 or less, often about 1.0 or less, and most often about 0.7 or less. + The number of water molecules in the solvation shell has been reduced by about 10% to about 15%, or alternatively about 15% to 20%, or alternatively about 20% to 25%, or alternatively about 25% to 30%, or alternatively about 30% to 35%, or alternatively about 35% to 40%, or alternatively about 40% to 45%, or alternatively about 45% to 50%, or alternatively about 50% to 55%, or alternatively about 55% to 60%, or alternatively about 60% to 65%, or alternatively about 65% to 70%, or alternatively about 70% to 75%, or alternatively at least about 75%.
[0045] It should be understood that the following concentrations of electrolyte salt are used throughout this disclosure when comparing the properties of a WISE and the electrolyte compositions of the present disclosure. Typically, the concentration (i.e., molar concentration) of electrolyte salt in a WISE is about 15.7 m to about 16 m, or alternatively about 16 m to about 17 m, or alternatively about 17 m to about 18 m, or alternatively about 18 m to about 19 m, or alternatively about 19 m to about 20 m, or alternatively about 20 m to about 22 m, or alternatively about 12 m to about 25 m, or at least about 25 m. In contrast, the concentration of electrolyte salt in the electrolyte compositions of the present disclosure is about 6 m to about 5.5 m, or alternatively about 5.5 m to 5.0 m, or alternatively about 5.0 m to 4.5 m, or alternatively about 4.5 m or less.
[0046] Additionally, the disclosed aqueous electrolyte composition, comprising 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O, stabilized water and formed a robust LiF / polymer bilayer solid-electrolyte interface ("SEI") from the reduction of both LiTFSI and CO(NH2)2, while KOH catalyzed the reduction of LiTFSI. Furthermore, the aqueous LiMn2O4||Li4Ti5O 12 The full cell exhibited high coulombic efficiency (99.9%) and excellent stability (>87% for 1000 cycles) without any pretreatment.
[0047] Solvation structure of 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O electrolyte: Salt-like diluents including urea and N-methylacetamide can bind water strongly without significantly increasing the viscosity. Amides can also reduce the activity of water by forming strong hydrogen bonds with H2O. It has been reported that the hydrogen bonds between amides and water are even stronger than those between H2O molecules. Furthermore, amides can also promote the formation of a strong SEI layer in aqueous electrolytes and reduce the viscosity of the electrolyte.
[0048] Many amides are green chemicals, low cost and non-flammable. In addition, amides such as urea form eutectic systems with both solid LiTFSI salt and liquid H2O solvent. To study the effect of adding a poor solvent, urea was selected as a representative of a non-flammable poor solvent or diluent. In particular, urea was added to WISE to form a dilute aqueous electrolyte with a wider electrochemical stability window. It should be appreciated that the cost of the resulting electrolyte composition is significantly lower compared to WISE, since a significantly lower amount of electrolyte salt is required when adding a poor solvent.
[0049] Because the phase diagram of the ternary CO(NH2)2-LiTFSI-H2O system is unknown, we first determined the liquid region in the ternary phase diagram of CO(NH2)2-LiTFSI-H2O. Figure 1 (shaded area). If the composition of CO(NH2)2-LiTFSI-H2O is in the shaded area, a homogeneous and clear solution can be obtained. For example, mixing solid urea and solid LiTFSI with a small amount of liquid H2O at room temperature resulted in a clear, homogeneous, transparent aqueous electrolyte solution of 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O, suggesting strong intermolecular interactions. Based on the ionic conductivity of the aqueous electrolyte, an electrolyte of 4.1 m in the ternary coordinate system was initially selected, but the content of LiTFSI was increased to 4.5 m and 5.1 m to further study the electrochemical stability window of the aqueous electrolyte. Table 1 below summarizes the compositions of selected CO(NH2)2-LiTFSI-H2O-0.1 m KOH electrolytes (denoted as 4.1 m, 4.5 m, and 5.1 m, respectively) with different LiTFSI salt molarities of 4.1 m, 4.5 m, and 5.1 m. 0.1 m KOH was added to these three electrolytes because KOH can promote the reduction of LiTFSI to form LiF SEI. Individual CO(NH2)2 and H2O, CO(NH2)2-H2O (0.4:1) eutectic electrolytes, and 21 m WISE were used as references.
[0050] Table 1. Composition of various electrolytes at 25°C [Table 1]
[0051] The intermolecular interactions between LiTFSI, CO(NH2)2 and H2O were investigated by vibrational analysis. Raman spectra of 4.1 m, 4.5 m, 5.1 m and eutectic CO(NH2)2-H2O aqueous electrolytes were obtained along with the Raman spectra of individual CO(NH2)2 and H2O. The Raman spectrum of pure CO(NH2)2 was used as the reference spectrum, which is in agreement with the data in the literature. The 1010 cm for CO(NH2)2 -1 The strong Raman band at 1006 cm corresponds to the symmetric C–N stretching vibration and is seen in the three CO(NH)-LiTFSI-H0-0.1 m KOH aqueous electrolytes (4.1 m, 4.5 m, and 5.1 m). -1 in the eutectic CO(NH) / H0 solution, it shifts to a lower wavenumber of 1004 cm -1 and shifted to lower frequencies. Due to the weaker intramolecular hydrogen bonds, the C-N bonds become longer and the corresponding vibrations shift to lower wavenumbers. The strong interaction between H2O and CO(NH2)2 was also reflected by the shift of the C=O and NH2 modes. Previously reported, -1 The band at 1540 cm mainly reflects NH2 deformation, but at lower frequencies (1540 cm -1 ) band has stronger C=O character. In the eutectic CO(NH2)2-H2O solution, both NH2 deformation and C=O wagging vibration are believed to shift to higher frequencies due to the increased hydrogen bond strength from CO(NH2)2-H2O intermolecular interactions. The addition of LiTFSI causes even larger shifts in the three electrolytes due to the strong interaction of LiTFSI with H2O. Thus, both LiTFSI and CO(NH2)2 can reduce H2O activity and stabilize H2O.
[0052] The strong CO(NH2)2-H2O interactions in the 4.1 m, 4.5 m, and 5.1 m electrolytes were also confirmed using Fourier transform infrared spectroscopy (FTIR), which showed an optical peak at 3348 cm -1 and 3445 cm -1Two strong bands of CO(NH2)2 were observed at 3600 cm-1. These two bands correspond to the NH2 stretching vibration and shift to higher frequencies in the 4.1 m, 4.5 m and 5.1 m aqueous electrolytes due to stronger hydrogen bonds. Furthermore, in the three aqueous electrolytes (4.1 m, 4.5 m and 5.1 m), the bands at around 3600 cm-1 were observed. -1 A visible band appeared at 2900 cm for H2O. -1 ~3700 cm -1 The new band is also seen at higher intensity in the eutectic CO(NH2)2 / H2O, suggesting that isolated H2O interacts with CO(NH2)2.
[0053] Also, 17 O nuclear magnetic resonance (NMR) spectroscopy was used to characterize the strong binding between CO(NH2)2 and HO. Briefly, the NMR spectrum at -1.31 ppm of bulk HO was 17 The O signal was negatively shifted from -0.13 ppm to -1.44 ppm when 50% CO(NH2)2 was added to H2O forming a eutectic solution, suggesting extensive interactions between H2O and CO(NH2)2. When 4.1 m, 4.5 m, and 5.1 m LiTFSI was added as the electrolyte salt, 17 The O signal is further shifted by -0.48, -0.5, and -0.53, respectively, and HO is shifted to Li + However, with increasing salt concentration, 17 The shift in the O signal is small due to the equilibrium of LiTFSI dissociation, which is due to the increase in the salt concentration of TFSI. - (744.5 cm -1 ) is confirmed by a very slight shift in the characteristic Raman band of CO(NH2)2. This result indicates that CO(NH2)2 can stabilize H2O more strongly than LiTFSI salt. Therefore, CO(NH2)2 can stabilize H2O instead of LiTFSI, thereby effectively reducing the amount of LiTFSI salt in water.
[0054] The solvation structure of the electrolyte was simulated using molecular dynamics (MD) as described in the Examples section below. MD calculations and simulations showed that when CO(NH2)2 was introduced into a LiTFSI-H2O electrolyte solution, the primary Li + It was shown that the structure of the solvation sheath changes. The coordination numbers of the 4.1 m, 4.5 m, and 5.1 m electrolytes are summarized in Figure 2. Detailed pair distribution functions and coordination numbers for the 4.1 m, 4.5 m, and 5.1 m electrolytes were studied. See, for example, Figures 3A-3C, respectively. In the 4.1 m electrolyte, each Li + is surrounded on average by 3.1 CO(NH2)2 molecules, 0.3 TFSI molecules, and only 0.6 H2O molecules. In contrast, in the 21 m WISE, each Li + On average, there are 2.5 molecules of H2O in the primary solvation sheath. Addition of CO(NH2)2 increases the number of Li molecules in the primary solvation shell of the lithium ion. + As an ionic coordinator, some of the water molecules are replaced by CO(NH2)2. This can be observed spectroscopically, for example by Raman and FTIR spectroscopy. The average coordination number of TFSI increases with increasing LiTFSI concentration. For example, for a 4.5 m electrolyte solution, the average coordination number of TFSI is 0.81, and for a 5.1 m electrolyte solution, the average coordination number of TFSI is 0.85. Thus, an aqueous electrolyte solution of 4.5 LiTFSI has a tetrahydrofuran complex with [Li(CO(NH2)2) 2.5 (H2O) 0.7 (TFSI) 0.8 Despite the different LiTFSI concentrations, 4.5 m and 5.1 m have almost the same Li +They have a common first-order solvation structure. In addition, hydrogen bonds can be easily observed in MD simulations. The hydrogen bonds between CO(NH2)2 and H2O can reduce H2O activity by minimizing the presence of interfacial H2O at the surface of the anode. This is believed to be due to the stronger hydrogen bonds between urea-water compared to water-water hydrogen bonds. In addition, the strong hydrogen bonds between urea and water suppress H2O activity due to the tighter coordination between urea and water compared to water-water hydrogen bonds. This reduction in water activity is believed to in turn lead to an expansion of the electrochemical stability window.
[0055] In some embodiments, the introduction of CO(NH2)2 also reduces the amount of aggregates (AGG). Therefore, in some embodiments, a small amount of KOH is added simultaneously with CO(NH2)2 to reduce the amount of TFSI. - The reduction of LiF was catalyzed to form a LiF solid-electrolyte interface (SEI).
[0056] Electrochemical properties of 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O electrolytes: The electrochemical stability windows of 4.1 m, 4.5 m and 5.1 m aqueous electrolytes were tested by linear sweep voltammetry (LSV) at a scan rate of 0.2 mV / s (Figure 4A). As shown in Figure 4A, the stability window of the electrolytes significantly expanded from 3.0 V to 3.3 V in WISE, and the cathodic potential shifted 0.4 V negatively from 1.9 V to 1.5 V. Figure 4B shows that the reduction at all concentrations starts at about 2.5 V (before the cathodic limit of 2.4 V according to the Pourbaix diagram for water at pH 10) and reaches a plateau at about 2.2 V. It is well accepted that lithium fluoride salt (LiTFSI) plays an important role in the formation of LiF-rich SEI. DFT calculations (FIG. 4D) also show that the reduction potential of LiTFSI is much higher than that of CO(NH2)2, suggesting the selective reduction of LiTFSI over CO(NH2)2. KOH further accelerates the reduction kinetics of LiTFSI. The important role of the KOH additive is clearly shown in FIG. 5A and FIG. 5B. A small plateau corresponding to the reduction of LiTFSI appears with the presence of KOH, demonstrating that KOH can accelerate the reduction kinetics of LiTFSI and generate LiF-rich SEI. The above [Li(CO(NH2)2) 2.5 (H2O) 0.7 (TFSI) 0.8 ] As shown in the solvation structure, the large solubilization ability of CO(NH2)2 results in a CO(NH2)2-dominated interphase chemistry rather than H2O. Here, the synergistic effect of LiTFSI, CO(NH2)2, and KOH contributes to a robust SEI layer that successfully pushes the cathodic limit to 1.5 V. The CV curves of the 4.5 m and 5.1 m electrolytes are nearly overlapping, but the relatively dilute 4.1 m electrolyte has a higher current density than the 0.18 mA / cm of either the 4.5 m or 5.1 m electrolytes. 2 0.26 mA / cm 2It can be seen that the 4.1 m electrolyte also shows a slightly higher current in the anodic scan (Fig. 4C). The 4.5 m aqueous electrolyte shows a slightly lower anodic limit (4.8 V) than WISE (4.9 V) due to the CO(NH2)2 oxidation reaction. To explore the possibility of electrolyte corrosion of aluminum, we examined CV (Fig. 6) with Al foil as the working electrode and SEM images of the Al foil after CV (held at 5.0 V for 3.0 h). It was observed that the corrosion of aluminum by LiTFSI was almost suppressed. In addition, surprisingly and unexpectedly, the 4.5 m LiTFSI-0.1 m KOH-CO(NH2)2-H2O aqueous electrolyte resulted in an expanded electrochemical window of 3.3 V.
[0057] The active electrode (Li4Ti5O 12 Cyclic voltammograms (CVs) of the Li4Ti5O, LiMn2O4 and LiVPO4F all showed characteristic redox peaks that were shifted upwards by about 0.2 V due to the Nernst shift, suggesting that the lithium ion activity in the 4.5 m electrolyte was as low as in the 21 m WISE. 12 The anode has been long sought after for aqueous lithium-ion batteries due to its fast reaction kinetics and long cycling stability. However, to date, this anode has not been used in aqueous electrolytes due to the "cathode challenge" (e.g., reduction potential in the range of 1.7 V to 1.9 V vs. Li). The use of extremely high concentrations (e.g., 63 m with gel passivation, or Li4Ti5O 12 Li on 1.3 Al 0.3 Ti 1.7 Previous strategies, such as adding PEG to aqueous electrolytes along with a (PO4)3 coating, have still not been successful in achieving the Li4Ti5O 12 It is not possible to achieve the high coulombic efficiency (>99.9%) desired for practical use of the anode. To date, Li4Ti5O has been proposed as an anode in aqueous electrolyte with high coulombic efficiency (e.g., >99.9%). 12Table 2 shows the practical load (1.5 mAh / cm) of the active material. 2 LiMn2O4||Li4Ti5O with the aqueous electrolyte of the present disclosure has significantly improved coulombic efficiency at low cathode excess (e.g., less than 20%) and low cathode excess (e.g., less than 20%). 12 A full cell is shown.
[0058] Table 2. Electrolyte and Li4Ti5O at 4.5 m 12 Comparison with other electrolytes reported for aqueous Li-ion batteries based on [Table 2]
[0059] Li4Ti5O after cycling in 4.5 m aqueous electrolyte 12 The composition of the SEI layer on the electrode was characterized using X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). 12 The electrodes were washed with dimethyl carbonate (DMC) prior to XPS analysis to remove residual electrolyte. The characteristic C 1s peak located at 284.2 eV is attributed to conductive carbon, while the CF3 peak at 293.0 eV is attributed to the PVDF binder in the anode composite. The signals detected in C 1s at 286.1 eV, N 1s at 400.0 eV, and O 1s at 232.6 eV belong to organic CON species originating from CO(NH2)2. The presence of trace amounts of Li2CO3 as a SEI component is supported by the 290.5 eV in C 1s and 530.5 eV in O 1s spectra, respectively. The formation of Li2CO3 is attributed to CNO formed by decomposition of CO(NH2)2 by nucleophilic attack under alkaline conditions. - , followed by CO3 2- Inorganic LiF is examined by an additional F 1s signal at 685.5 eV due to the reduction of LiTFSI. The residual F 1s signal at 688.5 eV can be assigned to the PVDF binder. Li4Ti5O before cycling12 The XPS pattern of the electrode was also measured for comparison, and no obvious Li2CO3 or LiF signals were detected.
[0060] ToF-SIMS spectra were collected in the range of 5 m / z to 60 m / z with negative polarity. 12 From the active material, m / z=16 (O - ), and 19(F) from the reduction of LiTFSI - ), decomposition of CO(NH2)2 (CO(NH2)2→CNO - →CN - , C2 - ) to 24(C2 - ) and 26(CN - ) fragments were observed, which is consistent with the XPS results. No observable secondary ion species from Li2CO3 were detected, suggesting that the amount of Li2CO3 was small. Li4Ti5O 12 The spatial distribution of species in the SEI on the surface was analyzed by ToF-SIMS depth profiling, revealing that Ga + The edge of a 1.3 μm deep crater sputtered by ions was shown. The concentration depth profile showed that CN - and F - The concentration of Li4Ti5O decreased rapidly upon etching. 12 O derived from active materials - A more detailed investigation revealed that LiF-related species (F - The concentration of LiF (CN) was shown to decrease from the surface to the bulk of the electrode with a lower concentration gradient than the organic species (CN), indicating that the organic species is mainly located at the outermost surface and the LiF species is located deeper in the surface layer. - The signal intensity was lower than that from the SEI in 4.5 m aqueous electrolyte with KOH additive, indicating that more LiF was produced with the KOH additive. In addition, the ToF-SIMS results also suggest the formation of an F-rich CEI layer on the LiMn2O4 cathode side.
[0061] In addition, cycled Li4Ti5O 12 The structure of the electrode was analyzed by high-resolution transmission electron microscopy (HRTEM) to further verify the LiF / polymer bilayer SEI. 12 The polymer / LiF bilayer SEI on the surface is different from the crystalline LiF SEI formed on Mo6S8 in WISE. CON species detected in XPS and CN species detected in ToF-SIMS results. - The amorphous character, together with the seeds, was attributed to the polyurea. Thus, Li4Ti5O 12 The SEI interfacial phase formed on the anode surface is a mixture of organic and inorganic species that primarily comprise LiF.
[0062] From the SEI composition analysis, one possible mechanism for the formation of the SEI is summarized in Fig. 7. First, TFSI reacts with OH - Nucleophilic attack in the presence of F - Under alkaline conditions, F - The anion is Li + At high potentials, the urea precipitates with the cations to form an inner LiF layer, and at low potentials, the urea electrochemically polymerizes to a polyurea on the outer surface of the LiF. Such a robust bilayer SEI with a LiF-rich inner layer and an organic outer layer is beneficial for stable performance.
[0063] 2.5V LiMn2O4||Li4Ti5O in 4.5 m electrolyte 12 and 2.6V LiVPO4F||Li4Ti5O 12 Electrochemical performance of full cells: As shown in FIG. 4, the structural and chemical analysis of the SEI layer showed that the LiVPOF and LiMnO cathodes, as well as the LiTiO 12 All redox peaks of the anode were located within the electrochemical stability window of the three aqueous electrolytes (4.1 μm, 4.5 μm, and 5.1 μm), indicating that a robust SEI was formed on the Li4Ti5O 12To further explore the aqueous electrolyte of this disclosure, Li4Ti5O 12 The anodes were combined with either LiMn2O4 or LiVPO4F cathodes to form full cells with P / N capacity ratios as low as 1.14. A slight excess of cathode electrode capacity was used to counteract irreversible lithium depletion during SEI formation.
[0064] LiMn2O4||Li4Ti5O 12 The electrochemical performance of the full cells was evaluated in aqueous electrolytes with different LiTFSI concentrations, namely, 5.1 m, 4.5 m and 4.1 m, see Figures 8A and 8B. The coulombic efficiency at a low rate of 0.2 C was applied to all the cells to monitor any side reactions that are also used in a real battery environment. As shown in Figure 8A, the LiMn2O4||Li4Ti5O 12 The full cell is relatively stable upon cycling even at 0.2 C and low P / N values, and the cell stability at 4.5 is much better than in 4.1 m electrolyte. The capacity of the full cell in 5.1 m electrolyte, which is slightly lower than in 4.5 m electrolyte, is due to the increased viscosity due to the increased salt concentration. Since the lithium source is limited in the full cell, the coulombic efficiency is important for cycling stability. As shown in Figure 8B, the LiMn2O4||Li4Ti5O in 4.1 m, 4.5 m, and 5.1 m electrolytes 12 The coulombic efficiencies of the full cells are 82.6%, 90.7% and 92.8%, respectively, in the first cycle, which gradually increase in the subsequent cycles and finally stabilize at 99.0% (4.1 m), 99.7% (4.5 m) and 99.8% (5.1 m).
[0065] Among the three electrolytes, the 4.5 m electrolyte has the best overall properties, i.e., relatively high ionic conductivity (1.0 mS / cm), low viscosity (0.32 Pa s) and wide electrochemical window (3.3 V). Thermal analysis of the 4.5 m electrolyte shows that it remains in a liquid state and is stable over a wide temperature range. Considering all these physicochemical properties and cost factors, the 4.5 m electrolyte was selected for more detailed studies.
[0066] Figure 8C shows the relationship between the concentration of LiMn2O4 and Li4Ti5O in 4.5 m of electrolyte at a high current of 0.5 C. 12 The long-term cycling performance of the full cell is shown. The full cell shows a discharge capacity of 61.3 mAh / g, corresponding to an anode capacity of 154.6 mAh / g and a cathode capacity of 101.6 mAh / g. The initial coulombic efficiency is high at 91.9% due to the formation of a highly insulating LiF-rich SEI. Hydrogen evolution was negligible or occurred only during the initial cycles and rapidly decreased. GC-MS of gases extracted from the cell cycled in 4.5 m aqueous electrolyte after the first cycle demonstrated the evolution of H2, corresponding to the hydrogen evolution reaction in the first cycle. The observed N2 and CO2 gases are attributed to the decomposition of urea. Ar is also the carrier gas for the device. After 20 cycles, the pouch cell was fully degassed and subsequently cycled for another 20 cycles. The GC-MS results show that no H2 gas was detected in the subsequent cycles. The coulombic efficiency rises to 99% within 5 cycles and finally achieves an average CE of 99.96% after 26 cycles. As expected, a long cycle life of over 1000 cycles is achieved. Impressively, the LiMn2O4||Li4Ti5O 12 The cell retains over 87% capacity even after 1000 cycles, when the polarization increases slightly (Figure 8D). In contrast, LiMn2O4||Li4Ti5O in 4.5 m electrolyte without KOH additive 12 The cells exhibit gradual capacity fade upon cycling.
[0067] The electrolyte design strategy disclosed herein can be applied to other amides with similar molecular structures, such as urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, and combination(s) thereof. For example, by replacing urea with N-methylacetamide, LiMn2O4||Li4Ti5O 12 The full cell also exhibits excellent stability with a high capacity retention rate (90% at 450 cycles).
[0068] LiVPO4F can deliver 142 mAh / g at 4.2 V, which corresponds to an energy density of 596 Wh / kg, 32% higher than LiMn2O4. LiVPO4F||Li4Ti5O at a low rate of 0.2 C 12 The coulombic efficiency of the full cell was 82.1% in the first cycle, and gradually increased in the subsequent cycles, eventually stabilizing around 99.2% (Figure 10). 12 The battery performance of the full cell was also cycled at a rate of 0.5 C in 4.5 mL of aqueous electrolyte (Figures 11A and 11B). The initial charge and discharge capacities were 64.1 mAh / g and 58.1 mAh / g (LiVPO4F+Li4Ti5O 12 The total mass of LiVPO4F||Li4Ti5O corresponds to an initial coulombic efficiency of 90.6%. The capacity retention is over 80% after 500 cycles. 12 The full cell is 2.5 V LiMn2O4||Li4Ti5O 12 It can provide a higher average voltage of 2.6 V compared to a full cell. 12 ) The full cell yields an energy density of 150.8 Wh / kg (total electrode mass).
[0069] LiMn2O4||Li4Ti5O 12To further evaluate the cell, LiMn2O4||Li4Ti5O 12 Pouch cell at 1.5 mAh / cm 2 The pouch cells were evaluated with a high areal capacity of 2.5 mAh / cm and a P / N capacity ratio of 1.14. The pouch cells showed an average coulombic efficiency of 99.97% and retained 88% of the capacity after 1000 cycles at 1 C, which is much better than all aqueous electrolytes reported so far (Table 2). The areal capacity was 2.5 mAh / cm. 2 This is clearly on par with commercial cell levels. The area capacity is now 1.5 mAh / cm 2 and 2.5 mAh / cm 2 LiMn2O4||Li4Ti5O 12 Typical galvanostatic charge-discharge curves at 1 C for the pouch cells were compared. This comparison showed that the polarization was relatively small at higher areal capacity. After electro-osmotic wetting at 2.0 V for 12 h with optimized external pressure (0.5 Mpa), the capacity was 2.5 mAh / cm. 2 LiMn2O4||Li4Ti5O 12 The pouch cell showed a high capacity retention of 72% after 500 cycles. The coulombic efficiency in the first cycle at 1 C was very high (93.6%) and rapidly increased to 99.9% at 50 cycles, indicating that the SEI formed in the first few cycles effectively inhibited water decomposition. The average CE from 10 to 500 cycles was 99.87%, which was due to the organic electrolyte LiMn2O4||Li4Ti5O 12 The initial capacity fade can be attributed to the consumption of Li in LiMn2O4 due to the formation of the SEI. 1.5 The low self-discharge rate demonstrates that the 4.5 m aqueous electrolyte allows the formation of a stable SEI and successfully suppresses side reactions, especially H2O decomposition.
[0070] LiMn2O4||Li4Ti5O at current densities of 1 C, 2 C, and 3 C 12The rate capabilities of the pouch cells showed reversible capacities of 58.6 mAh / g (92%), 46.9 mAh / g (74%), and 34.8 mAh / g (55%), respectively. The three-electrode pouch cells were used to distinguish the voltage and cycling behavior at the individual electrodes. Li4Ti5O 12 A cell consisting of the anode, LiMn2O4 cathode, lithiated LiFePO4 as a reference, membrane and 4.5 m aqueous electrolyte was cycled at 1 C for testing. The capacity fade is mainly due to the loss of active lithium in the LiMn2O4 cathode due to the formation of SEI. One way to improve the cycling performance is to use lithium-rich Li 1.5 The use of Mn2O4 as the cathode.
[0071] A visual comparison of electrolyte stability window and salt concentration of typical aqueous electrolytes is shown in FIG. 12. Surprisingly and unexpectedly, the disclosed electrolyte achieves an extended electrochemical stability window of 3.3 V without the use of ultra-concentrated salts. Using the disclosed electrolyte composition, an energy density of 103 Wh / kg was easily achieved at the level of 18650 type cells. This energy density is slightly higher than Ni-MH technology (100 Wh / kg). Considering other factors including voltage, rate capability, environmental compatibility, total cost and cycle life, it is reasonable to expect that the disclosed electrolyte will outperform current commercial aqueous technologies including lead acid, Ni-Cd and Ni-MH batteries.
[0072] The present disclosure provides an aqueous electrolyte containing a poor solvent that has an expanded electrochemical stability window to 3.3 V at significantly lower electrolyte salt concentrations (e.g., 4.5 mL iTFSI-KOH-CO(NH2)2-H2O aqueous electrolyte) over the 21 m WISE, which has an electrochemical stability window of 3.0 V. By adding a non-flammable organic poor solvent such as an amide, the aqueous electrolyte of the present disclosure can replace a portion of LiTFSI and maintain Li +The number of HO in the solvation shell is reduced from 2.6 in WISE to 0.7. Similar to LiTFSI salts, amide poor solvents such as urea suppress the activity of HO through strong hydrogen bonding interactions with water, and Li + It is believed that the small substitution of HO sites in the primary solvation shell may contribute to the formation of a robust SEI that includes an organic outer layer and a LiF-rich inner layer. Furthermore, the aqueous electrolytes of the present disclosure, such as 4.5 m LiTFSI-KOH-CO(NH)-HO, are capable of dissolving Li4Ti5O 12 The anode is coupled with both LiMn2O4 and LiVPO4F cathodes with a low P / N ratio of 1.14, allowing it to achieve high coulombic efficiency (>99.9%) and long cycling stability (up to 1000 cycles). In addition, it has a high areal capacity (2.5 mAh / cm 2 ), and P / N capacity ratio as low as 1.14, and excellent reversibility over 500 cycles with capacity retention of 72% can be fabricated using the aqueous electrolyte of the present disclosure. Thus, the aqueous electrolyte of the present disclosure provides a promising method to extend the electrochemical stability and enable the use of aqueous lithium-ion batteries in practical applications where both safety and low cost are crucial.
[0073] Additional objects, advantages, and novel features of the present disclosure will become apparent to those skilled in the art upon examination of the following examples of the present disclosure, which are not intended to be limiting, in which procedures presumably carried out are described in the present tense and procedures carried out in the laboratory are described in the past tense. EXAMPLES
[0074] Molecular Dynamics Simulations: All molecular dynamics (MD) simulations were performed using the Large-scale Atomic / Molecular Massively Parallel Simulator (LAMMPS, lammps.sandia.gov). To simulate the 4.1 m, 4.5 m, and 5.1 m electrolytes, LiTFSI, urea, and water molecules were added at 50 × 50 × 50 Å depending on the concentration. 3The properties of urea were evaluated using OPLS-AA parameters and RESP charges. + and TFSI - The known force field parameters of were used. See, for example, Wang et al., Nat. Commun., 7, pp. 1-9 (2016). The system was initialized using PACKMOL and Moltemplate (moltemplate.org). The simulation started with 2 ns NPT at 500 K, followed by 3 ns NPT at 330 K to completely dissolve the electrolyte. The system was then equilibrated in the NPT ensemble at 298 °K and 1 atm for 5 ns with a time step of 1.0 fs. The NPT calculated density (298 °K) is in good agreement with the experimentally measured density at room temperature, respectively. Finally, an MD run in the NVT ensemble was performed for 10 ns for equilibration, followed by a 10 ns NVT simulation to obtain the data. VMD software was used to visualize the snapshots and analyze the results.
[0075] Quantum chemical calculations: Quantum chemical (QC) calculations were performed using the Gaussian 09 software package to obtain reduction potentials. B3LYP density functional and 6-31+G ** The basis set is Li + The SMD implicit solvation model with acetone parameter (ε = 20.49) was used for the optimization of the complex structure. + For the calculation of solvation energies, M052X / 6-31G was used because it was found to have the best average performance for aqueous solvation energies in the original SMD study. * See, for example, Xu et al., J. Phys. Chem. A, 123, 7430-7438 (2019). Reduction potentials were calculated using the same method as disclosed in Borodine et al., in Nanotechnology, 26, p. 354003 (2015). Visualization of structures was performed using the VESTA software.
[0076] Electrode preparation and electrochemical measurements: Li4Ti5O 12 The anode, LiMn2O4 cathode and LiVPO4F cathode electrodes were provided by Saft Corporation. The LTO and LMO anodes were coated with high loadings on aluminum foil as current collectors: LTO at 1.5 mAh / cm 2 , LMO is 1.7 mAh / cm 2 For comparison, LiVPO4F (1.7 mAh / cm 2 ), LTO(2.5 mAh / cm 2 ) and LMO (2.8 mAh / cm 2 After calendaring, the LMO cathode and LTO anode had porosities of 40% and 30%, respectively. The thickness of the LMO increased from 90 μm to 135 μm with increasing loading. Similarly, the thickness of the LTO increased from 1.5 mAh / cm 2 At 80 μm, 2.5 mAh / cm 2 The electrodes were 1.2 cm in diameter. 2 The pouch cells were cut into sheets of 0.01 mm and dried under vacuum at 80 °C for 24 h before assembly. Electrochemical measurements were performed using 2032-type coin cells. Whatman glass fiber was used as the separator. For the pouch cells, aluminum and nickel strips were attached as electrode tabs on the cathode and anode sides, respectively. The electrolyte loading for each pouch cell was 0.02 mL / mAh. After the electrolyte was injected into the package, the battery was sealed under vacuum. Linear sweep voltammogram (LSV) tests were measured using a three-electrode cell with a Pt working electrode, a Pt counter electrode, and Ag / AgCl as the reference electrode. For the LSV measurements, a CHI660B electrochemical workstation was used with a scan rate of 0.2 mV s -1 Galvanostatic cycling of the assembled cells was performed using a Land CT2001A tester (Wuhan, China).
[0077] Ionic conductivity measurements of aqueous electrolytes: Ionic conductivity was measured by electrochemical impedance spectroscopy (EIS) using a Gamry workstation (Gamry 1000E, Gamry Instruments, USA) at a perturbation of 5 mV, with frequencies ranging from 0.01 Hz to 100000 Hz at room temperature. The conductivity cell constant was previously determined at room temperature using a 0.01 M KCl standard aqueous solution.
[0078] Sample characterization: Raman spectra were measured using a spectrophotometer at 1200 cm for all samples sealed in glass test tubes. -1 ~100cm -1 The spectra were collected at Labram Aramis, Horiba Jobin Yvon using a 532 nm diode-pumped solid-state laser. Fourier transform infrared spectroscopy (FTIR) was recorded on a NEXUS 670 FT-IR instrument. 17 O NMR spectrum in pure water 17 The chemical shift of the O nucleus was used as the 0 ppm reference, and the 17 NMR spectroscopy (XPS) experiments were performed on a Bruker DRX 500 spectrometer at 1000 nm frequency. All NMR measurements were performed at 296.2 K. X-ray photoelectron spectroscopy (XPS) experiments were performed on a high-resolution Kratos AXIS 165 X-ray photoelectron spectrometer using monochromated Al Ka radiation. All samples were retrieved from fully aqueous Li-ion batteries (ALIB) cells in a 2032-type coin cell configuration after electrochemical cycling. The samples were washed three times with DME and then dried under vacuum for 2 h before XPS measurements. The morphology of the samples was observed with a JEOL JEM 2100F transmission electron microscope (TEM) (100 kV) and a Hitachi High-Tech SU-70 field emission scanning electron microscope (FE-SEM) (5 kV).
[0079] The above discussion of the present disclosure has been presented for purposes of illustration and description. The above is not intended to limit the present disclosure to the form or forms disclosed herein. The description of the present disclosure includes one or more embodiments and descriptions of several variations and modifications, but other variations and modifications may be within the scope of the present disclosure, e.g., within the skill and knowledge of one of ordinary skill in the art after understanding the present disclosure. It is intended to be entitled to include alternative embodiments to the extent permitted, including alternative, interchangeable, and / or equivalent structures, functions, ranges, or steps to those claimed, regardless of whether such alternative, interchangeable, and / or equivalent structures, functions, ranges, or steps are disclosed herein, and without any intention to publicly dedicate them to any claimable subject matter. All references cited herein are incorporated by reference in their entirety.
[0080] Drawing translation Figure 1 Liquid liquid Urea Figure 2 Coordination number TFSI molality TFSI molar concentration Figure 3A all all urea Figure 3B all all urea Figure 3C all all urea Figure 4 Current density Voltage (V vs. Li / Li + ) Voltage (Li / Li + V for Current Current Li2TFSIcomplex Li2TFSI complex LiCO(NH2)2 complex Figure 5A Current density Voltage (V vs. Li / Li + ) Voltage (Li / Li + V for without KOH with KOH Figure 5B Current density Voltage (V vs. Li / Li + ) Voltage (Li / Li + V for with KOH without KOH Figure 6 Current density Voltage (V vs. Li / Li + ) Voltage (Li / Li + V for 1st 1st 2nd 2nd time 3rd 3rd time Figure 7 nucleophilicattack Polymerization Organic species Figure 8A Capacity Cycle Number Low rate Figure 8B Efficiency Cycle Number Figure 8C Capacity Cycle Number Efficiency average CE Figure 8D Voltage Capacity 1000th 1000th 100th 100th 1st 1st Figure 9A Capacity Cycle Number Efficiency average CE Charge Charge Discharge Figure 9B Voltage Capacity 450th 450th 100th 100th 1st 1st Figure 10 Capacity Cycle Number Efficiency Low rate Figure 11A Capacity Cycle Number Efficiency average CE Figure 11B Voltage Capacity 500th 500th 100th 100th 1st 1st Figure 12 Potential (V) vs Li / Li + Li / Li + Electric potential relative to (V) Traditional aqueous electrolyte super-concentrated
Claims
1. an electrolyte salt including a lithium salt; Water, A water-miscible organic compound; 1. A non-flammable aqueous electrolyte composition for a lithium ion battery comprising:
2. 2. The aqueous electrolyte composition of claim 1, wherein the organic compound is an amide.
3. The organic compound has the formula: R 1 -C(=O)-NR 2 R 3 (In the formula, R 1 is C 1 ~C 4 Alkyl, C 3 ~C 6 is a cycloalkyl or a moiety of formula -X, X is -OR a , -NR b R c or -SR a and R a are H or C 1 ~C 4 is alkyl, R b , R c , R 2 and R 3 each independently represents H or C 1 ~C 4 3. The aqueous electrolyte composition according to claim 1, wherein the aryl group is an alkyl group.
4. The lithium salt is LiCl, LiPF 6 , Li 2 SO 4 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 CH 3 ) 2 , LiN(SO 2 C 4 H 9 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiN(SO 2 C 4 F 9 ) 2 , LiN(SO 2 F 3 )(SO 2 C 4 F 9 ), LiN(SO 2 C 2 F 5 )(SO 2 C 4 F 9 ), LiN(SO 2 C 2 F 4 SO 2 ), LiN(SO 2 F) 2 , LiN(SO 2 F)(SO 2 CF 3 ), LiNO 3 , LiBF 4 , LiCF 3 SO 3 or a combination thereof.
5. The lithium salt is LiN(SO 2 CF 3 ) 2 The aqueous electrolyte composition of any one of claims 1 to 4, comprising:
6. The lithium salt is LiPF 6 , LiSO 3 CF 3 or a combination thereof.
7. 7. The aqueous electrolyte composition of claim 1, wherein the electrolyte salt further comprises a magnesium salt.
8. 8. The aqueous electrolyte composition of claim 1, wherein the molarity of the electrolyte salt is about 6 m or less.
9. 9. The aqueous electrolyte composition of claim 1, wherein the molarity of the electrolyte salt is about 5.5 m or less.
10. 10. The aqueous electrolyte composition of claim 1, wherein the molarity of the electrolyte salt is less than about 5 m.
11. 11. The aqueous electrolyte composition of claim 1, wherein the organic compound comprises urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or a combination thereof.
12. A cathode; An anode; an electrolyte composition comprising an electrolyte salt, water, and another compound miscible with water as a poor solvent; Includes a rechargeable lithium-ion battery.
13. 13. The rechargeable lithium ion battery of claim 12, wherein the electrochemical stability window of the electrolyte composition is greater than 3.0 V.
14. 14. The rechargeable lithium-ion battery of claim 12 or 13, wherein the aqueous electrolyte composition further comprises a hydroxide.
15. 15. The rechargeable lithium ion battery of any one of claims 12 to 14, wherein the hydroxide comprises KOH, NaOH, LiOH or a mixture thereof.
16. 16. The rechargeable lithium-ion battery of claim 12, wherein the molarity of the electrolyte salt in the electrolyte composition is less than 5 m.
17. 17. The rechargeable lithium ion battery of any one of claims 12 to 16, which is a pouch cell lithium ion battery or a coin cell lithium ion battery.
18. 18. The rechargeable lithium ion battery of any one of claims 12 to 17, wherein the rechargeable lithium ion battery has a coulombic efficiency of 99% or more after 5 cycles.
19. 19. The rechargeable lithium ion battery of any one of claims 12 to 18, wherein the capacity retention of the rechargeable lithium ion battery after 500 cycles is at least 90%.
20. 1. A rechargeable lithium ion battery comprising: a cathode; an anode; and an aqueous electrolyte composition having an electrochemical stability window greater than 3.0 V, wherein a molarity of an electrolyte salt in the aqueous electrolyte composition is less than 5 m.
21. 21. The rechargeable lithium-ion battery of claim 20, wherein the aqueous electrolyte composition comprises a lithium electrolyte salt, water, and a poor solvent that is miscible with water.
22. 22. The rechargeable lithium ion battery of claim 20 or 21, wherein the anti-solvent reduces the cathodic limiting potential by at least about 0.1 V.
23. 23. The rechargeable lithium ion battery of claim 21 or 22, wherein the poor solvent comprises an amide compound.
24. 24. The rechargeable lithium ion battery of claim 23, wherein the amide compound comprises urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or combinations thereof.
25. 25. The rechargeable lithium-ion battery of any one of claims 20 to 24, wherein the aqueous electrolyte composition further comprises a hydroxide.
26. 1. A method of increasing the electrochemical stability window in a lithium ion battery containing an aqueous lithium electrolyte solution, the method comprising adding a water-miscible poor solvent to the aqueous lithium electrolyte solution.
27. 27. The method of claim 26, wherein the anti-solvent comprises an amide compound.
28. 28. The method of claim 26 or 27, wherein the anti-solvent comprises urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or a combination thereof.
29. The antisolvent has the formula: R 1 -C(=O)-NR 2 R 3 (In the formula, R 1 is C 1 ~C 4 Alkyl, C 3 ~C 6 is a cycloalkyl or a moiety of formula -X, X is -OR a , -NR b R c or -SR a and R a are H or C 1 ~C 4 is alkyl, R b , R c , R 2 and R 3 each independently represents H or C 1 ~C 4 The method according to any one of claims 26 to 28, wherein the aryl group is alkyl.
30. 30. The method of any one of claims 26 to 29, wherein the amount of the electrochemical stability window is increased by at least about 0.2 V.
31. 1. A method for lowering the cathode limit potential in a lithium battery containing an aqueous lithium electrolyte solution, the method comprising adding a water-miscible anti-solvent to the aqueous lithium electrolyte solution.
32. 32. The method of claim 31 , wherein the anti-solvent comprises an amide compound.
33. 33. The method of claim 31 or 32, wherein the anti-solvent comprises urea, N-methylacetamide, acetamide, N,N-diethylmethacrylamide, N,N-dimethylacrylamide, tetramethylurea, N,N'-dimethylurea, 1,1-dimethylurea, 1,3-diethylurea, 1,1-diethylurea, or a combination thereof.
34. The antisolvent has the formula: R 1 -C(=O)-NR 2 R 3 (In the formula, R 1 is C 1 ~C 4 Alkyl, C 3 ~C 6 is a cycloalkyl or a moiety of formula -X, X is -OR a , -NR b R c or -SR a and R a are H or C 1 ~C 4 is alkyl, R b , R c , R 2 and R 3 each independently represents H or C 1 ~C 4 The method according to any one of claims 31 to 33, wherein the aryl group is alkyl.
35. 35. The method of any one of claims 31 to 34, wherein the amount of cathodic limiting potential is reduced by at least 0.1 V.
